MEMBANGUN PERSONAL BRANDING DI ERA DIGITAL PADA SISWA/SISWI SMK MUHAMMADIYAH PANGKALAN BALAI KECAMATAN BANYUASIN III KABUPATEN BANYUASIN - Dewi, Inne Miftah; Marhamah, Faila Sufa; Silvia, Yuni; Sari, Rafika (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2024)
Personal branding is a way of representing oneself by exploring one's potentials. It is fitting that the personal branding that is created must be clear, strong and attractive so that a person can give a deep impression to the public easily. In this digitalised world, one of the methods for developing personal branding can be done through seminars. Students of SMK Muhammadiyah Pangkalan Balai, Banyuasin Regency, received hands-on training from influencers as an effort to create their own self-image and dare to show their potential and build a confident race as a form of readiness to enter the world of work and the public. One of the activities in the seminar included providing tips on building personal branding by creating an attitude that is in accordance with norms and religion, utilising social media and applications that are widespread and easily accessible to students and applying this knowledge by publishing a curriculum vitae. Based on the results of this seminar, it can be concluded that the participants have understood the material presented. By showing a conducive atmosphere and high enthusiasm from the participants. And with the courage of the participants to express constraints by asking several questions to the speakers.